The use of mobile technology in health libraries: a summary of a UK‐based survey. (21st August 2015) - Chamberlain, David; Elcock, Martin; Puligari, Preeti
Abstract: Background: Health libraries have changed over the past fifteen years in the format of the information they provide. This is driven by developments in technology. Objectives: To conduct a survey of NHS health libraries in the United Kingdom in order to summarise how mobile technologies are being used, how they are promoted and how they are delivered, highlighting good practice and solutions to issues. Methods: An online survey was carried out in 2013 and sent to academic and NHS web‐based discussion lists. There were 199 responses. Results: Main replies were from large Acute Hospital Trusts. Only 18% of respondents had conducted research into use of mobile technology (MT) within their Trust. Forty per cent of Trusts offered clinical point of care tools, 29% mobile catalogues, and 30% had mobile enabled web sites. Libraries utilised third‐party partnerships rather than develop their own applications or tools. Seventy per cent of Trusts promoted new MT services via e‐mail. Network restrictions were the main barrier to development as well as finance and expertise. Conclusions: Uptake and development of MT is sporadic and driven by individuals. There is an opportunity for collaboration and sharing resources and expertise. There are benefits to adopting user‐friendly resources.